Narrow Band Imaging: A Novel Technique for Immediate Evaluation of Efficacy in Laparoscopic Radiofrequency Ablation of Exophytic Hepatocellular Carcinoma. Issue 5 (October 2018) - Seleem, Mohamed; Hassany, Mohamed
Abstract : Hepatocellular carcinoma (HCC) is the second leading cause of cancer mortality worldwide. Evolution of laparoscopic techniques helps to a great extent in facilitating and replacing the conventional surgical maneuvers. This article describes the novel use of narrow band imaging (NBI) in laparoscopic radiofrequency ablation (LRFA) of exophytic HCC to ensure its adequate ablation. In total, 11 patients with proven HCC were recruited to perform LRFA; NBI were applied during and after completion of ablation session, with NBI, the exophytic HCC appears dark green or blue in color and after start of LRFA; the tumor capsule turned into red color denoting hemoglobin coagulation and vascular damage; in 5 cases and after completion of ablation; the tumor capsule was still dark green or blue denting viability which necessitates needle repositioning and ablation continuation. NBI helps to a great extent in confirmation of successful ablation of exophytic HCC.